2020
DOI: 10.3390/ijerph17165924
|View full text |Cite
|
Sign up to set email alerts
|

Provincial Dietary Intake Study (PDIS): Micronutrient Intakes of Children in a Representative/Random Sample of 1- to <10-Year-Old Children in Two Economically Active and Urbanized Provinces in South Africa

Abstract: In 1999, the National Food Consumption Survey found serious risk of dietary deficiency for a number of micronutrients in 1- to 9-year-old children in South Africa. To address these shortfalls, fortification with vitamin A, thiamine, riboflavin, niacin, vitamin B6, folic acid, iron and zinc of maize meal and bread flour was made mandatory in 2003. The aim of this study was to examine micronutrient intakes of 1- to <10-year-old children after nearly 20 years of fortification in two of the most urbanized and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Having fewer unhealthy items in the home may also encourage children and adolescents to consume more F&V and lean meats [57]. This is important given that a number of national surveys in South Africa have shown that F&V intake is below recommendations in all age groups [58,59]. For example, results from the South African Provincial Dietary Intake Survey in 1 to >10-year-old children showed that salty snacks contributed a third of total energy intake (maize porridge contributed most to total energy intake), while also being the top source of total fat and saturated fat.…”
Section: Discussionmentioning
confidence: 99%
“…Having fewer unhealthy items in the home may also encourage children and adolescents to consume more F&V and lean meats [57]. This is important given that a number of national surveys in South Africa have shown that F&V intake is below recommendations in all age groups [58,59]. For example, results from the South African Provincial Dietary Intake Survey in 1 to >10-year-old children showed that salty snacks contributed a third of total energy intake (maize porridge contributed most to total energy intake), while also being the top source of total fat and saturated fat.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, it has been shown that refined maize meal is the staple food in the black African population and there is a higher intake of refined maize meal consumption in GTG than in WC. Consumption of white bread is the second most common high-energy commercial food which is also commonly consumed in both provinces although to a greater extent in the WC [24,25,46].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber intake was consistently below the EAR in all year groups. South African children have been shown to not meet the fruit and vegetable intake recommendations, be more likely to eat white rather than brown bread, to eat energy-dense nutrient-poor foods or snacks, i.e., salty snacks (crisps), sweet snacks (sweets, chocolate, cake, biscuits) and to drink sugar-sweetened beverages (SSBs), contributing to energy, carbohydrate and fat intake, without providing fiber [ 18 , 19 , 43 , 44 , 45 ]. Added sugar and trans-fat intakes also increased with age, but the increase was notably more prominent between the 1- and 2-year-olds, reflecting the possible increased exposure to energy-dense foods and drinks from two years of age onwards.…”
Section: Discussionmentioning
confidence: 99%